Recreational chemistry and the development of the capabilities of the area of science, technology and environment, Miraflores - Huamalies Huánuco-2011 - Bravo-Jara, Sonia (2019)
The present investigation had as its main objective to determine the influence of the "Chemistry" in the development of the capabilities of the area of Science, Technology and Environment of third-grade students of secondary education of the Educational Institution "Republic of Canada" Miraflores-2011. With the purpose of determining such influence was developed and implemented the pilot program entitled "Chemistry". The experimental group, it was made to the treatment, applying learning sessions with content" that were based on four fundamental principles; the principle of activity and freedom, the principle of socialization, the principle and the principle of realism, while the control group de- veloped the learning process using the traditional approach. The descriptive statistical analysis indi- cates that the averages that correspond to the post-test in the experimental group were higher than the control group, demonstrating that the application of the "chemistry" is influenced to a large extent on the level of achievement of the capabilities of the area of Science, Technology and Environment. The inferential statistical analysis using the mean difference using the Student's t distribution indicate that the value of the calculated t is located to the right (rejection) of the critical value is therefore that in all cases rejects the null hypothesis and accept the alternative hypothesis or research, as they have suffi- cient evidence to accept that Recreational Chemistry allows you to raise the level of achievement of the capabilities of the area of Science, Technology and Environment, thus making a significant learning of the students.